1993
DOI: 10.1111/j.1749-7345.1993.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Survival of Juvenile Orconectes virilis and Orconectes immunis at Different Temperatures1

Abstract: Culture of orconectid crayfishes in the midwestern USA offers the potential of contributing to a year‐round supply of fresh product as summer/fall production would augment winterhpring production in the southern USA. However, relatively little basic biological information exists for this potential new aquaculture crop. In this study, the authors reared juvenile (third instar) Orconectes virilis and Orconectes immunis at either 10, 15, 20, 25 or 30 C and measured weight gain and survival over a 21 day period. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Although O. luteus is one of the most common species found in the Ozarks, its higher thermal growth optimum compared to species restricted to the Ozarks may partly explain its occurrence in the warmer streams in northeastern Missouri (P ieger, 1996) and in west-central Illinois (Wetzel & Poly, 2000). That C max and growth scope for O. virilis increased from 18 ± C to 26 ± C and declined at 30 ± C is consistent with the results of a previous study which found that growth rates of juvenile O. virilis increased with increasing temperature from 10 ± C to 25 ± C, then declined at 30 ± C (Wetzel & Brown, 1993). Relations between water temperature and growth are known for only two other species of cray sh from the midwestern United States.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although O. luteus is one of the most common species found in the Ozarks, its higher thermal growth optimum compared to species restricted to the Ozarks may partly explain its occurrence in the warmer streams in northeastern Missouri (P ieger, 1996) and in west-central Illinois (Wetzel & Poly, 2000). That C max and growth scope for O. virilis increased from 18 ± C to 26 ± C and declined at 30 ± C is consistent with the results of a previous study which found that growth rates of juvenile O. virilis increased with increasing temperature from 10 ± C to 25 ± C, then declined at 30 ± C (Wetzel & Brown, 1993). Relations between water temperature and growth are known for only two other species of cray sh from the midwestern United States.…”
Section: Discussionsupporting
confidence: 88%
“…Relations between water temperature and growth are known for only two other species of cray sh from the midwestern United States. Like O. virilis, growth of juvenile O. immunis increased with temperature up to 25 ± C, then declined at 30 ± C (Wetzel & Brown, 1993). Juvenile O. rusticus, a species that has replaced indigenous cray shes in several locations in the central U.S. and Canada, have an optimum temperature for growth between 26 and 28 ± C (Mundahl & Benton, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that this temperature could be responsible for the minimal crayfish growth. In short-term experiments (<32 d), virile crayfish juveniles grew at least 60% at 20-21°C (Hill et al 1993, Wetzel & Brown 1993. Furthermore, daily consumption rates of virile crayfish are near their maximum at 22°C (Whitledge & Rabeni 2003).…”
Section: Discussionmentioning
confidence: 99%
“…virilis (cf. MOMOT, 1984;WETZEL and BROWN, 1993), O. immunis (cf. WETZEL and BROWN, 1993) and Pacifastacus leniusculus (WESTMAN, 1973).…”
Section: Introductionmentioning
confidence: 99%